THE EXPERIENCE OF MIDWIVES WHO EXPERIENCED THE TRAUMATIC CHILDBIRTH - Rayanti Sagala; Nining Febriana; Linda Dewanti (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: The high rate of medicalization in a woman reduces her ability to give birth and negatively impacts labor. Negative birth emotion in a midwife affects the quality of care. METHOD: This research is a descriptive qualitative research. The sampling technique was purposive sampling consisting of 10 respondents based on inclusion and exclusion criteria setted by the researcher. Data was obtained by conducting in-depth interviews. Data was analysed by reducing data, presenting data, coding, categorizing, and drawing conclusions. RESULTS: Three themes that identified the causes of labor trauma to midwives in this study were complications, pain during labor and post sc, and the absence of a baby sitter. Besides being caused by having previous illnesses, providers who are impatient and prioritize their agendas cause women experience complications that make them traumatized. The attitude of providers and things around women can influence women's perceptions of women's pain. The absence of a baby sitter causes theintense stress for women during pregnancy. CONCLUSION: Providers should have good effective communication skills and pay attention to women's mental readiness during pregnancy and birth. The government ensures that the services provided during childbirth focus on the needs of women so as to reduce the number of trauma.